The mouse olfactory peduncle. 2.The anterior limb of the anterior commissure - Brunjes, Peter (Frontiers in Neuroanatomy, 2013)
The central core of the olfactory peduncle (the tissue connecting the olfactory bulb to the forebrain) includes a white matter tract that extends caudally to the anterior commissure. The purpose of the present study was to examine this “anterior limb of the anterior commissure” (ALAC) to determine if the axons that progress through it segregate on the basis of their point of origin, neurotransmitter type, size or shape. While local differences in axon density were observed in the ALAC, they were not consistent between samples of the anterior and posterior peduncle, and no other compartmentalization within the tract was observed. The innervation of the caudal olfactory peduncle by neuromodulatory fibers was examined to determine if they enter the region via the ALAC. Cholinergic fibers densely filled the peduncle, followed in order by serotonergic, noradrenergic, histaminergic and orexinergic processes. Differences in the distribution of the fibers were noted for each system. While each axon type could be observed in the ALAC, it is probable that they enter the peduncle though several routes. Data for axon caliber in the ALAC was compared to information previously collected on the peduncle’s other white matter region, the lateral olfactory tract. Axons in the ALAC were smaller, suggesting that the olfactory system is organized with a fast system for distributing incoming sensory information and a more economical, distributed system for subsequent processing.